The correlation between variations of pressure against temperature distribution in supersonic subsea compact Wet-Gas Separators - Ahmad, M.F.A. (Trans Tech Publications Ltd, 2014)
Conventional wet gas separators are used as a mean to remove free water using gravitational and momentum principle. However, these separators create setback in terms of its efficiency. As an alternative, supersonic compact wet gas separator have been designed in Universiti Teknologi PETRONAS Gas Separation Research Center (UTP GSRC) which uses supersonic flow to separate natural gas and free water for gas transmission pipelines. For the preliminary design, it is important to determine the flow behavior according to the design of the separators. The results can provide information on whether the design can be accepted or improvement should be taken into consideration. It is therefore an objective of this paper to numerically simulate and analyze the correlation between variations of pressure against temperature distribution in the separators design. From the initial pressure variation against temperature results, it can be concluded that the initial pressure ranges from 5 MPa to 6.7 MPa are the best to be used for achieving better separation efficiency. Â© (2014) Trans Tech Publications, Switzerland.